2009
DOI: 10.1016/j.chemosphere.2009.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Simulated rainfall-driven dissolution of TNT, Tritonal, Comp B and Octol particles

Abstract: a b s t r a c tLive-fire military training can deposit millimeter-sized particles of high explosives (HE) on surface soils when rounds do not explode as intended. Rainfall-driven dissolution of the particles then begins a process whereby aqueous HE solutions can enter the soil and groundwater as contaminants. We dripped water onto individual particles of TNT, Tritonal, Comp B and Octol to simulate how surface-deposited HE particles might dissolve under the action of rainfall and to use the data to verify a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 13 publications
3
31
2
Order By: Relevance
“…However, after 35 days the fragile octol particle disintegrated in small pieces, which resulted in a higher surface area and an increased dissolution of both TNT and HMX. Similar disintegration of octol particles into smaller pieces under water flow has been recently observed by other researchers [13]. TNT was entirely dissolved after 80 days and only 5.5% of HMX remained to be dissolved after 238 days.…”
Section: Long Term Dissolution In Dripping Experimentssupporting
confidence: 87%
See 1 more Smart Citation
“…However, after 35 days the fragile octol particle disintegrated in small pieces, which resulted in a higher surface area and an increased dissolution of both TNT and HMX. Similar disintegration of octol particles into smaller pieces under water flow has been recently observed by other researchers [13]. TNT was entirely dissolved after 80 days and only 5.5% of HMX remained to be dissolved after 238 days.…”
Section: Long Term Dissolution In Dripping Experimentssupporting
confidence: 87%
“…Dissolution of explosives by precipitation is the departure point and one of the controlling factors for the transport, fate, and impact of explosives [8,9]. Moreover, few studies suggested that the dissolution rate of individual explosives was decreased when present in formulations compared to the pure explosives [10][11][12][13]. The primary goal of the present study was therefore to study the dissolution of GIM particles in aqueous media and compare results with the pure explosives, HMX and TNT, as well as octol (HMX/TNT: 70/30) in order to understand the effect of the binder and the interdependence of both explosives on their dissolution rates.…”
Section: E-mail Addressmentioning
confidence: 99%
“…3). Other studies have provided similar Composition B dissolution information [9,13,14,18]. However, because the RDX:TNT:HMX ratios in Composition B vary, we wanted to determine the formulation of Composition B that was used to detonate our samples.…”
Section: Dissolution Of Composition Bmentioning
confidence: 97%
“…This may be attributable to enhanced electron-reduction transformation in the presence of fresh, reactive mineral particle surfaces and/or to the presence of an active microbiological regime on fresh soil particle surfaces. The dissolution of Composition B (RDX and TNT with minor HMX) particles, and the desorption and dissolution of explosive detonation residuals, has been quantified and modeled based on particle sizes and the effect of rainfall to better simulate the temporal fate of explosive residues in training range ecosystems [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The material and equation of state models of projectiles shell are the same as wing structure. Comp B [11] is selected as the internal explosive due to its efficient killing effect. As mentioned in section 2, the material model of the explosive is *ELASTIC-PLASTIC-HYDRO and the equation of state is *IGNITION-GROWTH-OF-REACTION-IN-HE.…”
Section: Damage Mechanismmentioning
confidence: 99%